Análisis comparativo de la inteligencia artificial ChatGPT y Google Chrome. - Bazurto Oyola, Jorge Alexander (2023)
Artificial Intelligence (AI) platforms assist users in learning and processing data by analyzing large amounts of information, helping to make decisions and understand needs. Processes require clear and accurate information. They generate knowledge through AI tools, assist users in making better future decisions, however, there are different systems on the market and the choice must be made based on needs, adaptability and compatibility to the environment, etc. Among the compared platforms, the objective of the study was achieved, which focused on analyzing, comparing and evidencing the best data integrity and information management tool that helps to improve the performance of the solutions to the user's needs. In the present study a bibliographic and comparative methodology was applied, with clear information from authors, as well as interacting directly with both platforms. Presenting a favorable solution to what was investigated in documents and reports, reaching the expected result in this study, in such a way that it was known which is the best platform to work together with the user. After the analysis it can be concluded, that the best option is the Artificial Intelligence ChatGPT, considering the characteristics of the AI system, such as Natural Language Processing Capability, Adaptability, Wide range of knowledge, Accuracy, etc.